Konsep Optimisme pada Karakter Arrietty dalam Film Animasi Jepang “The Secret World of Arrietty (2011)” - Mu’alim Nur Ahsan; Syihabuddin Syihabuddin (Peneliti.net, 2023)
This study discusses how an animated character presents a concept of optimism that usually exists in humans. This research is descriptive qualitative research, in which the researcher examines the attitude of Arrietty's character which is in accordance with the concept of optimism. The data source for this research comes from an animated film made by Studio Ghibli entitled